OPTIMALISASI PROSES DAN HASIL PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) PADA SEKOLAH DASAR (SD) / MADRASAH IBTIDAIYAH (MI) - Irjan, Irjan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
The survey result of International Monitoring Studies has done by TIMSS (Third International Science and Mathematics Study) at 2005 in science education domain (1) Analysis of content structure, (2) Research on teaching and learning, (3) Development and evaluation ofÂ instruction/Instructional design, dan (4) Research on curriculer issue and science education policies, has reported that quality of science (IPA) learning in Indonesia is still leaved than others state in Asia, even Asia Tenggara. Therefore, we should evaluate totality concerning with learning process of science, especially in SD/MI and the steps concretely which is able to perform to identify a variety of obstacle of science learning and his solution with the result that is able to increase the process and the result of science learning at SD/MIKeyword: Learning, Science, SD/MI